Two-stage processing of liquid hot water pretreatment for recovering C5 and C6 sugars from cassava straw. (December 2018) - Lyu, Huisheng; Zhou, Jinyi; Geng, Zhongfeng; Lyu, Chunliu; Li, Yonghui
Graphical abstract: Fig. 1 Schematic of the two stage LHW pretreatment and enzymatic hydrolysis. Highlights: A two-stage method using LHW pretreatment was studied. Optimized conditions of 180 ℃ and for 60 min for 1st stage LHW. Optimized conditions of 200 ℃ and for 20 min for 2nd stage LHW. C5 sugars yield of 83.15%% by two-stage LHW pretreatment. Enzymatic hydrolysis of C6 sugars yielded 85.02%. Abstract: In this study, two-stage process using liquid hot water pretreatment (LHW) was proposed to recover C5 and C6 sugars from cassava straw. In the 1st stage, biomass was treated at varying temperatures (160–200 °C) and reaction time (15–105 min). In the 2nd stage, the remaining solid after 1st stage was treated under various reaction conditions (190–210 °C, 30–90 min). After two-stage LHW pretreatment, the pretreated solid contained a large amount of cellulose and subsequently was highly digested by cellulase. The optimal pretreatment conditions were 180 ℃ and for 60 min (LogRo of 4.13) for 1st stage pretreatment, and 200 ℃ and for 20 min (LogRo of 4.25) for 2nd stage pretreatment. The yield of C5 sugars of 83.15% by two-stage LHW pretreatment. Meanwhile, using 31 mg/g glucan- CTec2 enzyme to treat remaining solid after the two-stage treatment, the yield of C6 sugars achieved 85.02%.